THE IMPACT OF COVID-19 OUTBREAK ON SCHOOL E-LEARNING SYSTEM (Isagoge - Journal of Humanities and Social Sciences, 2022)
In any operation of the world, advanced technology plays a vital role. Consequently, the e-learning system encourages and plays a role as a substitute system in the teaching-learning process due to the pandemic of COVID-19. This study explores the e-learning access by students through identifying the Strengths, Weaknesses, Opportunities, and Challenges (SWOC) analysis during the COVID-19 pandemic period. The simple random sampling technique was utilized to select the participant students at Kalkudah Educational Zone, Batticaloa district. The primary data were collected from 300 secondary school students through a questionnaire to collect data in line with the aim of the study for quantitative analysis to interpret the performance of SWOC. This study revealed, Strengths: the majority of (55%) of students familiarized to use social media for the teaching-learning process in the COVID-19 pandemic period. Weaknesses: the majority (59%) of students could not use the ICT to learning certain subjects such as Maths, Sciences and practical part of other subjects. Opportunities: a great (90%) usage of smartphones for education purposes. Challenges: more majority (80%) of students do not have competencies in using smartphones and unstable networks. Also, the majority (57%) of students’ families have economic challenges in having smartphones. Further, the study also showed that ICT skills among students have improved and that the availability of smartphones at the national level has increased during this pandemic period. The recommendations of the study: improve the ICT competencies of teachers and students in the education system, and the Ministry of Education needs to consider providing smartphone facilities under the free education system of Sri Lanka.
Keywords: Covid 19; E-learning; Secondary School